Transcriptional profiling of Anopheles gambiae mosquitoes for adult age estimation. - Cook, P; Sinkins, S (2010)
The age distribution of female mosquitoes in the field is a critical component of vectorial capacity because of the extrinsic incubation period of mosquito-borne pathogens. However this parameter has not been well characterized in malaria vectors because of methodological difficulties; transcriptional profiling provides a potential new approach for age determination. In Anopheles gambiae, microarrays were used to examine global gene expression over adult life. Nine genes were selected from the 2714 gene transcripts that displayed age-related transcription patterns, and quantitative reverse transcription PCR used to select the four best performing genes. The resulting age estimation assay was able to predict female age from lab-reared samples with sufficient accuracy to provide a potentially useful tool for studies of malaria epidemiology and control.